PERANCANGAN SISTEM INFORMASI TPQ BERBASIS WEBSITE DENGAN EVALUASI USABILITY MENGGUNAKAN METODE SUS (STUDI KASUS : TPQ AL-MUWAHHIDIN KOTA BIMA) - Fitri Aryani (LPPM Universitas Abdurrab, 2026)
Because the administrative management of the TPQ at the Al-Muwahhidin Grand Mosque in Bima City is still done manually, there is no way to manage data on students, instructors, class schedules, payments, and the dissemination of information. The objective of this study is to develop a web-based TPQ information system that allows for the evaluation of usability levels using the System Usability Scale (SUS) method. The system development method employed is the Software Development Life Cycle (SDLC), specifically using the Waterfall model. Black Box Testing was used to test the system. The SUS evaluation involved 43 participants, including administrators, instructors, and parents of students. The results of the Black Box testing showed that all system functions operated with a 100 percent success rate. For the SUS evaluation, the average score of 70.58 fell into the “Acceptable,” “Grade C,” and “Good” categories. The research results indicate that the information system can help manage and disseminate information at the TPQ more efficiently and effectively.